Role of Law Students in Providing Legal Literacy through Street Law - Mulyani, Leni Widi (The Indonesian Journal of International Clinical Legal Education, 2019)
Clinical Legal Education (CLE) is one of the programs that develop softskills for law students so that after graduation they’ll be ready to useand have a good spirit in helping others. The target group of theprogram are poor and/or marginalized who need help to get an accessto justice. CLE program consists of several activities, while the clinicwhich developed by the Faculty of law Pasundan University Bandung isthe provision of legal aid in the form of learning the law or the legalknowledge to those in need.